2021
DOI: 10.1002/cb.1970
|View full text |Cite
|
Sign up to set email alerts
|

An examination of personality traits as predictors of electronic word‐of‐mouth diffusion in social networking sites

Abstract: Nowadays, in the technological era, social networking sites (SNSs) have the capacity to influence, through electronic word‐of‐mouth (eWOM), consumers' attitudes towards brands and companies. Consequently, eWOM via SNSs has become an important marketing communication tool for facilitating consumer interaction, acquiring new customers, and enhancing customer loyalty. However, despite the extensive research conducted to identify and depict the antecedents of eWOM, the prediction of whether and to what extent bran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 114 publications
(191 reference statements)
0
21
0
Order By: Relevance
“…Secondly, our model does not take into account the potential moderating role of consumers’ psychographic characteristics. Previous studies (e.g., [ 31 ]) have suggested that personality traits (e.g., extraversion, self-esteem, etc.) have a significant impact on how consumers use social media, and on how they relate to brands within social networking platforms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, our model does not take into account the potential moderating role of consumers’ psychographic characteristics. Previous studies (e.g., [ 31 ]) have suggested that personality traits (e.g., extraversion, self-esteem, etc.) have a significant impact on how consumers use social media, and on how they relate to brands within social networking platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to offline word of mouth, eWOM, especially if generated through social media, has a faster and larger penetration because individuals tend to have many more friends and acquaintances virtually than they do offline [ 31 ].…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…According to Bhattacharyya and Bose (2020) , the concepts of environmental and social parameters are distinct from one another, but they are connected ( Matthes et al, 2020 ). According to Williams et al (2020) , people who give more weight to the importance of collective, or prosocial, values are more likely to be concerned about the environment and hold stronger pro-environmental beliefs ( Moisescu et al, 2021 ). According to the theory put forth by Tajvidi et al (2020) , for individuals to engage in pro-environmental behavior, they need to stop thinking only about themselves and start thinking about the larger society as a whole.…”
Section: Literature and Research Hypothesesmentioning
confidence: 99%
“…Thus, materialism had an impact on the status perception of individuals on SNS [ 28 ]. Besides, recent research on trait materialism has also shown the influence on posting behaviour [ 29 ], e-WOM diffusion [ 30 ], and SNS intensity among users [ 31 ].…”
Section: Introductionmentioning
confidence: 99%